In-vivo sclera thickness measurements in experimental myopia of guinea pigs - Ruiheng Zhang; Chuyao Yu; Li Dong; Yitong Li; Xuhan Shi; Haotian Wu; Wenda Zhou; Heyan Li; Wenbin Wei (BMC Ophthalmology)
Abstract The sclera is the target organ of axial elongation during myopia onset and progression. Visualizing the sclera in-vivo is important for monitoring the dynamic changes of the sclera remodeling in experimental myopia. In the present study, three-week-old tricolor guinea pigs were subjected to negative controls (n = 8), monocular negative lens-induced myopia (LIM, n = 10), or combining monocular LIM and intravitreally mTORC1 agonist (MHY1485, 4 µg) injection for inducing high myopia (LIM + MHY1485 group, n = 10) for four weeks. Serial biometric measurements were performed to monitor experimental myopia onset and progression. Swept-source optical coherence tomography (SS-OCT) was performed to measure sclera thickness at the beginning and end of study. The results showed four weeks of LIM and LIM + MHY1485 induced a significant degree of myopia shift, compared to the negative control (Control, -2.04 ± 0.60; LIM − 6.21 ± 0.55; LIM + MHY1485, -9.14 ± 1.11, diopters, P < 0.0001). The cross-sectional SS-OCT showed clear boundaries of the inner and outer boundaries of the sclera. At baseline, the mean sclera thickness was 105.05 ± 5.41 μm. At the end of the study, sclera thickness significantly correlated with axial length (coefficient = -4.49 μm for every 0.1 mm axial length increase, 95%CI: -3.56 to -5.83 μm, P < 0.001) and refractive error (coefficient = -2.77 μm for every 1 diopter myopic shift, 95%CI: -2.06 to -3.47 μm, P < 0.001) among all guinea pigs. Sclera thickness also significantly correlates with choroidal thickness and choroidal vascularity index (%). In conclusion, the present study shows SS-OCT can be used as a non-invasive method to evaluate sclera thickness and monitor myopia progression in the guinea pig model of LIM.